Preparation method of thin-film capacitor and thin-film capacitor

By depositing SrBi2Ta2O9 seed layer, sol-gel spin coating in thin film capacitors, forming the main film layer, magnetron sputtering deposition of flexible inner electrode and flexible dielectric layer, and performing staged annealing and rapid thermal annealing treatment, the solution is solved The lack of performance of traditional film capacitors in high-frequency and flexible electronic devices has achieved the effect of high stability, low leakage current and mechanical flexibility.

CN119522040APending Publication Date: 2025-02-25HANGZHOU DIANZI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411636771.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional film capacitors face problems such as high dielectric loss, large leakage current, insufficient mechanical flexibility and performance degradation in high-frequency circuits, ferroelectric memory and flexible electronic equipment, and are difficult to meet the high stability and high-frequency operation needs of future electronic systems.

Method used

The SrBi2Ta2O9 seed layer was deposited on the substrate by MOCVD process, combined with the sol-gel spin coating process to form the main film layer, and the flexible dielectric layer of the flexible inner electrode and ceramic matrix was deposited by magnetron sputtering, and phased annealing and rapid thermal annealing were adopted. The film is processed and the electrode is encapsulated using copper or silver material.

Benefits of technology

It improves the uniformity of the film and crystal orientation, improves the ferroelectric performance and insulation of the capacitor, enhances mechanical flexibility and long-term durability, reduces leakage current and energy loss, and is suitable for applications in high-frequency and flexible electronic equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the preparation method of the thin-film capacitor and the thin-film capacitor, an SBT seed layer is deposited on a substrate through an MOCVD technology, the uniformity and crystal orientation of a thin film are ensured, and therefore the ferroelectric performance and insulativity of the capacitor are improved; the thickness control and the high dielectric constant of the thin film are further ensured by combining the main film layer formed by a sol-gel spin coating process; the flexible inner electrode is deposited through magnetron sputtering, and the flexible dielectric layer of the ceramic substrate is superposed, so that the capacitor can still operate stably under the bending condition. And a staged annealing and rapid thermal annealing (RTA) mode is adopted, so that stress and defects in the film layer are effectively reduced, and the structural stability and long-term durability of the film are enhanced. And during packaging, a copper or silver electrode is used, and nickel plating and tin plating treatment is carried out, so that the conductivity and corrosion resistance of the electrode are improved, and the service life of the capacitor is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of film capacitors, and in particular, relates to a method for preparing a film capacitor and a film capacitor. Background Art

[0002] With the rapid iteration of electronic technology, higher requirements are placed on the high performance, miniaturization and durability of electronic components. Especially driven by the Internet of Things, 5G communications, automotive electronics and wearable devices, thin film capacitors have become one of the key components. This type of capacitor needs to maintain stable dielectric properties in high-frequency circuits, efficiently store and quickly read data in ferroelectric memories, and must have a certain degree of mechanical flexibility in flexible electronic devices to adapt to the bending and deformation of the working environment. However, traditional thin film capacitors still face multiple challenges in their applications in these fields, such as high dielectric loss leading to unstable signal transmission, large leakage current increasing energy loss and shortening device life, and insufficient mechanical flexibility limiting their widespread application in flexible electronic products. In addition, traditional thin film deposition processes, such as sputtering and physical vapor deposition (PVD), usually have difficulty in achieving high uniformity and stable ferroelectric properties of the film layer, which causes the performance of the capacitor to degrade during long-term operation and cannot meet the high stability and high-frequency operation requirements of future electronic systems.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a thin film capacitor and a thin film capacitor, thereby solving the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0006] A method for preparing a film capacitor comprises the following steps:

[0007] Step (1): using oxygen and argon plasma to treat the surface of the substrate for 6-10 minutes respectively, then placing the plasma-treated substrate in an MOCVD device to deposit a SrBi2Ta2O9 seed layer at a temperature of 400-450°C;

[0008] Step (2): preparing a mixed sol containing Sr, Bi and Ta, and spin coating it on the SBT seed layer at a speed of 2500-3000 rpm to form a uniform main film layer, and then annealing the spin-coated film at 200-300° C. for 8-10 minutes to obtain a SrBi2Ta2O9 film;

[0009] Step (3): evaporating a nano-scale metal film on the SBT main film layer, and depositing a flexible inner electrode by a magnetron sputtering process, and finally, superimposing a flexible dielectric structure of a ceramic matrix on the SrBi2Ta2O9 film to obtain a composite film;

[0010] Step (4): annealing the composite film using a staged annealing process. After the annealing is completed, the film capacitor is packaged with copper or silver materials for electrodes, and nickel and tin plating are performed in sequence.

[0011] Optionally, the substrate in step (1) is one of a Pt substrate, a Ti substrate, a SiO2 substrate, and a Si substrate.

[0012] Optionally, the thickness of the SBT seed layer deposited by MOCVD in step (1) is 20 to 50 nanometers.

[0013] Optionally, the step (2) of preparing a mixed sol containing Sr, Bi and Ta is:

[0014] Step (201): adding ethanol as a solvent into a beaker, and heating the solvent to 40-50° C.;

[0015] Step (202): adding strontium nitrate, bismuth nitrate and tantalum pentachloride as metal sources into the solvent and mixing them evenly to form a mixed solution;

[0016] Step (203): adding citric acid as a complexing agent to the mixed solution, and finally adjusting the pH value of the solution to between 4 and 5 using dilute ammonia water.

[0017] The molar ratio of strontium nitrate, bismuth nitrate and tantalum pentachloride is 1:2:2, and the molar ratio of the mixed solution and citric acid is 1:1.

[0018] Optionally, the step of depositing the flexible inner electrode by magnetron sputtering process in step (3) is:

[0019] Step (301): fix the sample substrate on the sample stage of the magnetron sputtering apparatus, and ensure that the sample is flat and the distance between the sample and the sputtering target is uniform;

[0020] Step (302): Start the vacuum system and evacuate the sputtering chamber to 10 -6 Pa, then, high-purity argon is filled as sputtering gas, and the gas pressure is adjusted to 0.1-1Pa;

[0021] Step (303): After the vacuum system is adjusted, radio frequency is applied to form a plasma discharge between the metal target and the substrate, and then argon ions bombard the target under the action of the electric field, sputtering out metal atoms, which fly in a straight line to the surface of the SBT film and form a flexible internal electrode thereon.

[0022] Optionally, the target material is one of gold, silver or platinum, and the thickness of the flexible inner electrode in step (3) is 50-100 nanometers.

[0023] Optionally, the step of annealing the composite film using a staged annealing process in step (4) is:

[0024] Step (401): after the film layer is deposited, annealing is first performed at 500° C. for 30 minutes to promote the formation of a preliminary crystal structure of SBT, and then annealing is performed at 650° C. for 1 hour to complete the first annealing;

[0025] Step (402): After the first annealing is completed, the composite film is placed in an RTA device and heated to 750°C, treated at a heating rate of 50°C / s, and maintained for 60 seconds before being placed in a cooling device and cooled to room temperature within 3-5 minutes.

[0026] A thin film capacitor prepared by the method for preparing a thin film capacitor comprises a substrate layer, an SBT seed layer, an SBT main film layer, an inner electrode layer, and a flexible dielectric layer which are arranged in sequence from bottom to top and are coated by a packaging layer.

[0027] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0028] The present invention deposits an SBT seed layer on a substrate through an MOCVD process, ensuring the uniformity and crystal orientation of the film, thereby improving the ferroelectric properties and insulation of the capacitor; the main film layer formed by the sol-gel spin coating process further ensures the thickness control and high dielectric constant of the film; magnetron sputtering deposits a flexible inner electrode and a flexible dielectric layer superimposed with a ceramic matrix, so that the capacitor can still operate stably under bending conditions. The use of staged annealing and rapid thermal annealing (RTA) effectively reduces the stress and defects in the film layer, and enhances the structural stability and long-term durability of the film. Copper or silver electrodes are used during packaging and nickel and tin plating are performed, which not only improves the conductivity and corrosion resistance of the electrodes, but also extends the service life of the capacitor. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] In this embodiment, a method for preparing a thin film capacitor is provided, comprising the following steps:

[0035] Step (1): using oxygen and argon plasma to treat the surface of the substrate for 6-10 minutes respectively, then placing the plasma-treated substrate in an MOCVD device to deposit a SrBi2Ta2O9 seed layer at a temperature of 400-450°C;

[0036] Step (2): preparing a mixed sol containing Sr, Bi and Ta, and spin coating it on the SBT seed layer at a speed of 2500-3000 rpm to form a uniform main film layer, and then annealing the spin-coated film at 200-300° C. for 8-10 minutes to obtain a SrBi2Ta2O9 film;

[0037] Step (3): evaporate a nano-scale metal film on the SBT main film layer, and deposit a flexible inner electrode by a magnetron sputtering process. Finally, superimpose a flexible dielectric structure of a ceramic matrix on the SrBi2Ta2O9 film to obtain a composite film; the ceramic dielectric is aluminum oxide or zirconium oxide.

[0038] Step (4): annealing the composite film using a staged annealing process. After the annealing is completed, the film capacitor is packaged with copper or silver materials for electrodes, and nickel and tin plating are performed in sequence.

[0039] In this embodiment, the substrate in step (1) is one of a Pt substrate, a Ti substrate, a SiO2 substrate, and a Si substrate.

[0040] In this embodiment, the thickness of the SBT seed layer deposited by MOCVD in step (1) is 20 to 50 nanometers.

[0041] In this embodiment, the step (2) of preparing a mixed sol containing Sr, Bi and Ta is as follows:

[0042] Step (201): adding ethanol as a solvent into a beaker, and heating the solvent to 50° C.;

[0043] Step (202): adding strontium nitrate, bismuth nitrate and tantalum pentachloride as metal sources into the solvent and mixing them evenly to form a mixed solution;

[0044] Step (203): adding citric acid as a complexing agent to the mixed solution, and finally adjusting the pH value of the solution to between 4 and 5 using dilute ammonia water.

[0045] The molar ratio of strontium nitrate, bismuth nitrate and tantalum pentachloride is 1:2:2, and the molar ratio of the mixed solution and citric acid is 1:1.

[0046] In this embodiment, the step of depositing the flexible inner electrode by magnetron sputtering process in step (3) is as follows:

[0047] Step (301): fix the sample substrate on the sample stage of the magnetron sputtering apparatus, and ensure that the sample is flat and the distance between the sample and the sputtering target is uniform;

[0048] Step (302): Start the vacuum system and evacuate the sputtering chamber to 10 -6 Pa, then, high-purity argon is filled as sputtering gas, and the gas pressure is adjusted to 0.1-1Pa;

[0049] Step (303): After the vacuum system is adjusted, radio frequency is applied to form a plasma discharge between the metal target and the substrate, and then argon ions bombard the target under the action of the electric field, sputtering out metal atoms, which fly in a straight line to the surface of the SBT film and form a flexible internal electrode thereon.

[0050] In this embodiment, the target material is one of gold, silver or platinum, and the thickness of the flexible inner electrode in step (3) is 50-100 nanometers.

[0051] In this embodiment, the step (4) of annealing the composite film using a staged annealing process is as follows:

[0052] Step (401): after the film layer is deposited, annealing is first performed at 500° C. for 30 minutes to promote the formation of a preliminary crystal structure of SBT, and then annealing is performed at 650° C. for 1 hour to complete the first annealing;

[0053] Step (402): After the first annealing is completed, the composite film is placed in an RTA device and heated to 750°C, treated at a heating rate of 50°C / s, and maintained for 60 seconds before being placed in a cooling device and cooled to room temperature within 3-5 minutes.

[0054] The present invention will now be further described in detail with reference to embodiments.

[0055] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.

[0056] Example 1: Preparation of SBT thin film capacitor based on Pt substrate, comprising the following steps:

[0057] After treating the Pt substrate with oxygen and argon plasma for 6 minutes respectively, a 30-nanometer-thick SBT seed layer was deposited at 450°C in an MOCVD device; subsequently, a mixed sol containing Sr, Bi and Ta (molar ratio 1:2:2) was prepared and spin-coated on the seed layer at a speed of 3000 rpm, annealed at 300°C for 8 minutes, and the spin-coating and annealing operations were repeated to obtain an SBT main film layer; a nanoscale metal film was evaporated on the main film layer, and a 50-nanometer-thick gold inner electrode was deposited by a magnetron sputtering process, and a flexible dielectric structure of a ceramic matrix was superimposed to form a composite film; after the film layer deposition was completed, it was first annealed at 500°C for 30 minutes to promote preliminary crystal formation, and then annealed at 650°C for 1 hour to reduce stress; finally, the composite film was placed in an RTA device and heated to 750°C, treated at a heating rate of 50°C / s for 60 seconds, and cooled to room temperature within 3 minutes. Copper material was used as an electrode during packaging, and nickel and tin plating were performed.

[0058] The remanent polarization intensity is measured using a ferroelectric analyzer or PE loop tester to measure the polarization and depolarization cycle of the capacitor when an electric field is applied, and the polarization value during depolarization.

[0059] The forced electric field is tested synchronously with the PE loop line by gradually increasing the electric field and recording the electric field value when the polarization is reversed. The leakage current density is measured by using a Keithley 2400 Source Meter at a constant voltage. The calculation formula is J = I / A, where I is the measured current and A is the electrode area.

[0060] The dielectric constant is obtained by frequency scanning using an Agilent 4284ALCR Meter, measuring capacitance at 1kHz and using the formula Calculate, is the film thickness, ε0 is the vacuum dielectric constant.

[0061] The insulation breakdown field strength is calculated by gradually increasing the voltage until the film breaks down and recording the breakdown voltage. The calculation formula is E bd =V bd / d.

[0062] The fatigue endurance test was completed on a ferroelectric analyzer by continuously switching the polarity under a fixed electric field for 10 9 After that, record the decrease ratio of the residual polarization intensity. The test results are:

[0063] Remanent polarization intensity: 8.4μC / cm 2

[0064] Forced electric field: 80kV / cm

[0065] Leakage current density: 2.0×10 -8 A / cm 2

[0066] Dielectric constant: 190 (1kHz)

[0067] Insulation breakdown field strength: 320V / μm

[0068] Fatigue tolerance: 10 9 After the first switching cycle, the residual polarization decreases by no more than 5%.

[0069] High remnant polarization: good data storage capability, suitable for high-performance ferroelectric memory applications.

[0070] Low leakage current density: ensures the film has excellent insulation properties, reduces power consumption and extends service life.

[0071] In the ultra-thin SBT film capacitor based on Pt substrate, the synergistic effect of various materials is specifically reflected in: the Pt substrate not only provides high conductivity, but also has oxidation resistance and good adhesion, ensuring the stable combination between the electrode and the film, while reducing stress accumulation and avoiding performance degradation at high temperature; the ferroelectric structure formed by Sr, Bi, and Ta elements in the SBT film provides excellent ferroelectric and dielectric properties, supporting data storage and high-frequency applications, and achieving uniform deposition and excellent insulation of the film through the MOCVD process; the gold (Au) inner electrode reduces leakage current in frequent switching operations with its high conductivity and stability, and maintains the long-term stability of the capacitor; staged annealing improves crystal orientation and reduces stress, and RTA treatment further eliminates residual defects in the film and optimizes electrical properties. The coordinated effect of these materials ensures that the capacitor has high residual polarization, high dielectric constant, low leakage current and excellent fatigue tolerance, which is particularly suitable for high-reliability applications in high-frequency circuits and ferroelectric memories.

[0072] Example 2: Preparation of SBT thin film capacitor based on Ti substrate, comprising the following steps:

[0073] After treating the Ti substrate in oxygen and argon plasma for 8 minutes respectively, a 20 nm thick SBT seed layer was deposited at 420°C in an MOCVD device; a mixed sol containing Sr, Bi and Ta was prepared, heated to 45°C, citric acid was added as a complexing agent, the pH was adjusted to 4.5, and spin-coated on the seed layer at a speed of 2800 rpm, and annealed at 250°C for 9 minutes to obtain a uniform SBT main film layer; subsequently, a 100 nm thick silver inner electrode was deposited using a magnetron sputtering process, and a flexible medium of an alumina matrix was superimposed; after the film layer was deposited, it was first annealed at 500°C for 30 minutes, and then annealed at 650°C for 1 hour to complete the preliminary annealing, and then heated to 750°C at a heating rate of 50°C / s in an RTA device, kept warm for 60 seconds, and cooled to room temperature within 5 minutes; finally, the electrodes were encapsulated with silver material, and nickel and tin plating were performed in sequence.

[0074] The remanent polarization intensity is measured using a ferroelectric analyzer or PE loop tester to measure the polarization and depolarization cycle of the capacitor when an electric field is applied, and the polarization value during depolarization.

[0075] The forced electric field is tested synchronously with the PE loop line by gradually increasing the electric field and recording the electric field value when the polarization is reversed. The leakage current density is measured by using a Keithley 2400 Source Meter at a constant voltage. The calculation formula is J = I / A, where I is the measured current and A is the electrode area.

[0076] The dielectric constant is obtained by frequency scanning using an Agilent 4284ALCR Meter, measuring capacitance at 1kHz and using the formula Calculate, d is the film thickness, ε0 is the vacuum dielectric constant.

[0077] The insulation breakdown field strength is calculated by gradually increasing the voltage until the film breaks down and recording the breakdown voltage. The calculation formula is E bd =V bd / d.

[0078] The fatigue endurance test was completed on a ferroelectric analyzer by continuously switching the polarity under a fixed electric field for 10 9 After that, record the decrease ratio of the residual polarization intensity. The test results are:

[0079] Remanent polarization intensity: 7.8μC / cm 2

[0080] Forced electric field: 85kV / cm

[0081] Leakage current density: 2.5×10-8A / cm 2

[0082] Dielectric constant: 180 (1kHz)

[0083] Insulation breakdown field strength: 300V / μm

[0084] Fatigue tolerance: The remnant polarization decreases by about 6% after 109 switching cycles.

[0085] In the ultra-thin SBT film capacitor based on Ti substrate, the synergistic effect of various materials is specifically reflected in: the Ti substrate provides good mechanical strength and thermal stability, closely combines with the SBT film, and enhances the durability of the overall structure; the Sr, Bi, and Ta ternary structure of the SBT film gives it a high dielectric constant and stable ferroelectric properties, which is suitable for the application of ferroelectric memory; the silver (Ag) inner electrode not only has good conductivity, but also has corrosion resistance, ensuring consistency in mass production; the Al2O3 flexible dielectric layer improves mechanical flexibility and stress resistance, and extends the service life of the capacitor in a deformation environment; the phased annealing and RTA process improves the crystal quality, eliminates film defects, and improves the overall electrical performance. The combination of these materials enables the capacitor to have good mechanical strength, high dielectric properties and durability while maintaining low cost, which is suitable for high-voltage electronic components and sensors with frequent switching operations.

[0086] Example 3: Preparation of SBT thin film capacitor based on SiO2 / Si substrate, comprising the following steps:

[0087] After treating the SiO2 / Si substrate in oxygen and argon plasma for 10 minutes respectively, a 50-nanometer-thick SBT seed layer was deposited at 400°C in an MOCVD device; the solution was heated to 40°C, citric acid was added, the pH was adjusted to 5 using dilute ammonia water, and it was spin-coated on the seed layer at a speed of 2500rpm, annealed at 200°C for 10 minutes, and the spin coating and annealing were repeated to obtain the SBT main film layer; then, a 75-nanometer-thick platinum inner electrode was deposited on the SBT main film layer by a magnetron sputtering process, and a flexible dielectric layer of a zirconium oxide matrix was superimposed; after the film layer was deposited, it was first annealed at 500°C for 30 minutes, and then annealed at 650°C for 1 hour to optimize the crystal structure, and then placed in an RTA device and heated to 750°C at a heating rate of 50°C / s, kept warm for 60 seconds, and cooled to room temperature within 3 minutes; finally, the electrodes were encapsulated with copper material, and nickel and tin plating were performed to complete the preparation of the thin film capacitor.

[0088] The remanent polarization intensity is measured using a ferroelectric analyzer or PE loop tester to measure the polarization and depolarization cycle of the capacitor when an electric field is applied, and the polarization value during depolarization.

[0089] The forced electric field is tested synchronously with the PE loop line by gradually increasing the electric field and recording the electric field value when the polarization is reversed. The leakage current density is measured by using a Keithley 2400 Source Meter at a constant voltage. The calculation formula is J = I / A, where I is the measured current and A is the electrode area.

[0090] The dielectric constant is obtained by frequency scanning using an Agilent 4284ALCR Meter, measuring capacitance at 1kHz and using the formula Calculate, d is the film thickness, ε0 is the vacuum dielectric constant.

[0091] The insulation breakdown field strength is calculated by gradually increasing the voltage until the film breaks down and recording the breakdown voltage. The calculation formula is E bd =V bd / d.

[0092] The fatigue tolerance test was completed on a ferroelectric analyzer. After switching the polarity continuously for 109 times under a fixed electric field, the decrease ratio of the residual polarization intensity was recorded. The test results are as follows:

[0093] Remanent polarization intensity: 6.9μC / cm 2

[0094] Forced electric field: 90kV / cm

[0095] Leakage current density: 3.0×10 -8 A / cm 2

[0096] Dielectric constant: 170 (1kHz)

[0097] Insulation breakdown field strength: 290V / μm Fatigue tolerance: After 109 switching cycles, the residual polarization decreases by about 8%.

[0098] Example 3, the ultra-thin SBT film capacitor based on SiO2 / Si substrate achieves excellent performance through the synergy of multiple materials. Specifically: the SiO2 / Si substrate provides stable support and good insulation performance, effectively reducing leakage current; the SBT film ensures high dielectric constant and residual polarization performance, and remains stable during multiple switching cycles; the platinum (Pt) inner electrode provides excellent conductivity and high temperature resistance, reduces electrochemical corrosion and enhances current conduction; the ZrO2 flexible dielectric layer imparts mechanical flexibility and stress resistance, making the capacitor suitable for curved electronic devices; staged annealing and RTA treatment eliminate internal stress and defects, and improve the structural stability and electrical properties of the film. The combination of these materials ensures that the capacitor has lightweight, high storage capacity, low power consumption, good insulation and long-term stability.

[0099] The SiO2 / Si substrate has the advantages of lightweight and low cost, and is suitable for large-scale integrated circuits and consumer electronics. It also provides good insulation performance to prevent leakage. After the SBT film is deposited on this substrate, it still maintains a high dielectric constant and stable residual polarization performance, meeting the needs of storage and high-frequency applications. The platinum (Pt) inner electrode used in the capacitor has excellent conductivity and high temperature resistance, ensuring its stability in harsh environments. To further improve the mechanical flexibility, the capacitor introduces a ZrO2 flexible dielectric layer to enable it to adapt to bent and deformed electronic devices. Through staged annealing and rapid thermal annealing (RTA), the internal stress of the film is effectively reduced, and its structural stability and insulation performance are improved. The synergistic effect of this material system not only ensures the lightweight, low cost and insulation performance of the capacitor, but also gives it high heat resistance and good fatigue tolerance, which is very suitable for lightweight and integrated large-scale consumer electronics production.

[0100] A thin film capacitor prepared by the method for preparing a thin film capacitor comprises a substrate layer, an SBT seed layer, an SBT main film layer, an inner electrode layer, and a flexible dielectric layer which are arranged in sequence from bottom to top and are coated by a packaging layer.

[0101] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A method for preparing a thin film capacitor, characterized in that: The following steps are involved: Step (1): using oxygen and argon plasma to treat the surface of the substrate for 6-10 minutes respectively, then placing the plasma-treated substrate in an MOCVD device to deposit a SrBi2Ta2O9 seed layer at a temperature of 400-450°C; Step (2): preparing a mixed sol containing Sr, Bi and Ta, and spin coating it on the SBT seed layer at a speed of 2500-3000 rpm to form a uniform main film layer, and then annealing the spin-coated film at 200-300° C. for 8-10 minutes to obtain a SrBi2Ta2O9 film; Step (3): evaporating a nano-scale metal film on the SBT main film layer, and depositing a flexible inner electrode by a magnetron sputtering process, and finally, superimposing a flexible dielectric structure of a ceramic matrix on the SrBi2Ta2O9 film to obtain a composite film; Step (4): annealing the composite film using a staged annealing process. After the annealing is completed, the film capacitor is packaged with copper or silver materials for electrodes, and nickel and tin plating are performed in sequence.

2. The method for preparing a thin film capacitor according to claim 1, characterized in that: The substrate in step (1) is one of a Pt substrate, a Ti substrate, a SiO2 substrate, and a Si substrate.

3. The method for preparing a thin film capacitor according to claim 1, characterized in that: The thickness of the SBT seed layer deposited by MOCVD in step (1) is between 20 and 50 nanometers.

4. The method for preparing a thin film capacitor according to claim 1, characterized in that: Step (2) The steps of preparing a mixed sol containing Sr, Bi and Ta are: Step (201): adding ethanol as a solvent into a beaker, and heating the solvent to 40-50° C.; Step (202): adding strontium nitrate, bismuth nitrate and tantalum pentachloride as metal sources into the solvent and mixing them evenly to form a mixed solution; Step (203): adding citric acid as a complexing agent to the mixed solution, and finally adjusting the pH value of the solution to between 4 and 5 using dilute ammonia water.

5. The method for preparing a thin film capacitor according to claim 4, characterized in that: The molar ratio of strontium nitrate, bismuth nitrate and tantalum pentachloride is 1:2:2, and the molar ratio of the mixed solution and citric acid is 1:

1.

6. The method for preparing a thin film capacitor according to claim 1, characterized in that: The step of depositing the flexible inner electrode by magnetron sputtering process in step (3) is as follows: Step (301): fix the sample substrate on the sample stage of the magnetron sputtering instrument, and ensure that the sample is flat and the distance between the sample and the sputtering target is 70 cm; Step (302): Start the vacuum system and evacuate the sputtering chamber to 10 -6 Pa, then, high-purity argon is filled as sputtering gas, and the gas pressure is adjusted to 0.1-1Pa; Step (303): After the vacuum system is adjusted, radio frequency is applied to form a plasma discharge between the metal target and the substrate, and then argon ions bombard the target under the action of the electric field, sputtering out metal atoms, which fly in a straight line to the surface of the SBT film and form a flexible internal electrode thereon.

7. The method for preparing a thin film capacitor according to claim 6, characterized in that: The target material is one of gold, silver or platinum, and the thickness of the flexible inner electrode in step (3) is 50-100 nanometers.

8. The method for preparing a thin film capacitor according to claim 1, characterized in that: The steps of annealing the composite film using a staged annealing process in step (4) are as follows: Step (401): after the film layer is deposited, annealing is first performed at 500° C. for 30 minutes to promote the formation of a preliminary crystal structure of SBT, and then annealing is performed at 650° C. for 1 hour to complete the first annealing; Step (402): After the first annealing is completed, the composite film is placed in an RTA device and heated to 750°C, treated at a heating rate of 50°C / s, and maintained for 60 seconds before being placed in a cooling device and cooled to room temperature within 3-5 minutes.

9. A thin film capacitor prepared by the method for preparing a thin film capacitor according to any one of claims 1 to 8, characterized in that: It includes a base layer, an SBT seed layer, an SBT main film layer, an inner electrode layer, and a flexible dielectric layer which are arranged in sequence from bottom to top and are covered by a packaging layer.